PEMBUATAN BIODIESEL DARI BIJI KARET DENGAN KATALISATOR BUANGAN PROSES PERENGKAHAN MINYAK BUMI PERTAMINA UP III - Roni, Ahmad; Gusmiatun, Gusmiatun; Legiso, Legiso (Universitas katolik Musi Charitas, 2020)
Rubber seeds are an alternative raw material for biodiesel with great potential in Indonesia. Thisis because Indonesia is one of the largest rubber producers in Asia. Rubber seed oil has not beenwidely used. Therefore, this rubber seed oil needs to be processed, among others by reactingrubber seed oil with alcohol or by using an alcoholysis process, using Pertamina unit III petroleumcracking waste catalyst, which is also a waste, so that it can be utilized. The purpose of this serviceis in addition to applying the results of myCompetitive Grant research (Kiagus Ahmad Roni) whichwas funded by DIKTI in 2013-2014, also to provide knowledge and examples to the people ofSukajadi village, Prabumulih Timur sub-district, Prabumulih city, Muara Enim district, thisservice is proposed to be funded. by DIKTI for 2020, in 2015 this service was funded by DIKTI tobe implemented in Sumber Harum Village, Tunggal Jaya District and Margarahayu Village,Muara Telang District, Musi Banyu Asin Regency (MUBA) in processing rubber seeds to makethem more useful. The method used is Partipatory Action Research. This activity includesoutreach, mentoring and piloting in the community. The output targets to be achieved areScientific Articles of Proceedings in National scientific meetings (National Seminar onCommunity Service), Mass Media Articles of Local Print / Electronic Mass Media (SumatraExpress)